Ethnobotany of Zingiberaceae in Mae Hong Son, Northern Thailand - ANGKHANA INTA; CHUSIE TRISONTHI; WITTAYA PONGAMORNKUL; PRATEEP PANYADEE (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Inta A, Trisonthi C, Pongamornkul W, Panyadee P. 2023. Ethnobotany of Zingiberaceae in Mae Hong Son, Northern Thailand. Biodiversitas 24: 2114-2124. Zingiberaceae (ginger family) is one of the most important used plant families in Thailand. In this study, the uses of ginger species among the ethnic groups in Mae Hong Son province, northern Thailand, was investigated, which aims to answer these questions: how much diversity of ginger species is being used by the ethnicities in northern Thailand; which use categories are a most important use of ginger species? and which species or genera are the most important? The qualitative and quantitative ethnobotanical investigations were conducted with informants through semi-structured interviewing during a walk-in-the-woods in the forest around the villages and home gardens. The importance of each ginger species was compared using the ethnobotanical indices, including use-report (UR), cultural importance index (CI), fidelity level (FL), and informant agreement ratio (IAR). Therefore, 1,218 use reports of local Zingiberaceae were recorded, belonging to six use categories; 33 native ginger species of 9 genera were found. Food and medicine are the two most dominant use categories, with 572 and 446 use reports, respectively. According to the number of UR and CI, the most important local Zingiberaceae species were Zingiber purpureum, Curcuma longa, Alpinia galanga, Z. officinale, Z. ottensii, Z. rubens and Amomum siamense, respectively. About half of the ethnomedicinal ginger species found in this study were first reported for their medicinal properties.